Why firms purchase property insurance☆ - AUNONNERIN, D; EHLING, P (Journal of Financial Economics, 2008)
We investigate whether corporate finance incentives affect the extent of corporate hedging with property insurance. Using a database that contains detailed insurance information, we document a positive relation between the expected costs of distress and property insurance coverage. We also show that the dividend payout ratio is negatively associated with property insurance coverage, consistent with the view that firms with high payout ratios insure a smaller fraction of properties due to cash flows in excess of investment needs, easy access to capital markets, or both. Different incentives are important for the insurance deductible and limit of coverage, and the deductible and limit of coverage are substitutes.